PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA UMKM RUMAH SNACK ANUGRAH KABUPATEN TANGERANG - Rhomadhon, Sahrul; Ratnawati, Whina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the Influence of Leadership Style and Work Environment on the Performance of Employees of UMKM Rumah Snack Anugrah Tangerang Regency. In this study using a quantitative method with an associative approach. The population is all researchers totaling 50 employees. Sampling using saturated sampling techniques. The data analysis methods used are validity test, reliability test, multiple linear regression, determination coefficient analysis, correlation coefficient analysis (r), classical assumption test, and hypothesis test t test, f test. The results of the t test show that leadership style has a calculated t value> t table (20.047> 2.012) from a significant value of 0.001 <0.005, this means that leadership style significantly influences employee performance. The work environment has a calculated t-value > t-table (15.681 > 2.012) with a significance value of 0.001 < 0.005 and a significance value of 0.001 < 0.05, indicating a significant influence of the work environment on employee performance. Meanwhile, the F-test showed a calculated F-value of 232.363 > 3.20 (calculated F-value > F-table) and a significance value of 0.001 < 0.05, indicating a significant influence of leadership style and the work environment on employee performance. The coefficient of determination test (r-square) was 0.908, indicating a significant influence between work motivation and work discipline on employee performance of 90.8%. The remaining 9.2% was influenced by other factors not examined